PEMBUATAN BIOETANOL DENGAN TEKNI IMOBILISASI SEL Saccharomyces cerevisiae DARI LIMBAH KERTAS HVS - Dea Prisca Amanda; Marlinda Marlinda; Ramli Ramli; Andri Kurniawan (Politeknik Negeri Samarinda, 2021)
Paper production in Indonesia based on the Center for Pulp and Paper (BBPK) reaches 12.98 million tons/year. Paper that has been used and thrown away can cause problems for the environment. The cellulose content in paper is very high so that it can be used as a raw material for bioethanol. The fermentation technique used is modern biotechnology, namely the cell immobilization method. This method uses an inert material that is not soluble in the substrate. The purpose of this study is to determine the effects of the concentration of immobilized saccharomyces cerevisiae cells on bioethanol levels to increase the levels of bioethanol produced. Paper was hydrolyzed with 2N HCl to break down cellulose into glucose which would be used as a substrate. The research variable used was the concentrations of immobilized saccharomyces cerevisiae cells, namely 0, 5, 10, 15, 20, and 25% (w/w) in substrate. Fermentation was carried out in a batch system for 4 days. Immobilization of saccharomyces cerevisiae cells was made using 10% Na-Alginate and 7% CaCl2. Ethanol concentration was analyzed using gas chromatography and cell number analysis using gravimetry. The results showed the maximum concentration of bioethanol at a concentration of 15% cell immobilization. Where the concentration of bioethanol was 8.1876% and the number of cells was 1.84 g cells/LKeywords: bioethanol, fermentation, immobillization, paper, saccharomyces cerevisiae